2021
DOI: 10.1101/2021.01.09.21249508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploration of interethnic variation in the ibuprofen metabolizing enzyme CYP2C9: a genetic-based cautionary guide for treatment of COVID-19 symptoms

Abstract: Coronavirus disease 2019 (COVID-19), is a rapidly spreading infectious illness that causes a debilitating respiratory syndrome. Supportive therapy remains the standard for mild-to-moderate cases, including treatment with non-steroidal anti-inflammatory drugs (NSAIDs) e.g. ibuprofen, however such medications may increase COVID-19 complications when used in patients with acute viral respiratory infections. P450 enzyme CYP2C9 are known to be involved in the metabolism of NSAIDs, however, their pharmacogenetic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To further increase complexity, recent data show genetic variations of cytochrome P450 liver oxidative enzyme systems can influence the metabolism of NSAIDs, potentially affecting their elimination from the body, their tissue concentrations, and the greater risks of adverse events 19 . Genetic variations differ between ethnic groups, meaning, for example, that the risk of higher-thanexpected plasma drug levels may be greater in some populations than others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further increase complexity, recent data show genetic variations of cytochrome P450 liver oxidative enzyme systems can influence the metabolism of NSAIDs, potentially affecting their elimination from the body, their tissue concentrations, and the greater risks of adverse events 19 . Genetic variations differ between ethnic groups, meaning, for example, that the risk of higher-thanexpected plasma drug levels may be greater in some populations than others.…”
Section: Discussionmentioning
confidence: 99%
“…Based on limited preclinical data, it was hypothesized that NSAIDs (particularly ibuprofen, which is available worldwide over the counter [OTC] and the most commonly used NSAID) may be detrimental to patients with COVID-19 due to upregulation of angiotensin-converting enzyme (ACE) 2 expression, which, in turn, may facilitate viral entry into host cells and enhance pathogenicity of the viral load 14,18 . This concern was reported in the British Medical Journal, and despite a lack of evidence to confirm such risk, there was a significant reduction in NSAID use at a time when they could have benefitted those infected with COVID-19 [19][20][21] . In England, the National Health Service suggested that, in the absence of clear evidence, patients should be advised to take paracetamol to treat the symptoms of COVID-19 in preference to NSAIDs 22 .…”
Section: Introductionmentioning
confidence: 99%
“…CYP2C9 is known to be involved in the metabolism of NSAIDs, such as ibuprofen, that are commonly prescribed drug for the management of pain and fever. CYP2C9 varies substantially across ethnic groups, influencing drug responses and toxicity, where European populations are more likely to show impaired ibuprofen metabolism than Sub-Saharan and East Asian populations [ 116 ]. NSAIDs could be harmful to patients with COVID-19 as it upregulates angiotensin-converting enzyme 2 (ACE2) receptors in multiple organs, which serve as COVID-19 virus entry points into cells [ 21 ].…”
Section: Drugs Used To Treat Covid-19mentioning
confidence: 99%